Integrated multitrophic culture of shrimp Litopenaeus vannamei and tilapia Oreochromis niloticus in biofloc system: A pilot scale study - Holanda, Mariana; Ravagnan, Elisa; Lara, Gabriele; Santana, Gabriel; Furtado, Plinio; Cardozo, Alessandro; Wasielesky, Wilson; Poersch, Luis Henrique (Frontiers in Marine Science, 2023)
Shrimp production in biofloc systems generates excess organic matter that must be removed from the system. Due to its ability to consume natural productivity, the integration of tilapia in shrimp culture could help to reduce the levels of total suspended solids in the biofloc system. The present study aimed to evaluate two stocking densities of tilapia in an integrated culture with shrimp Litopenaeus vannamei reared in a pilot-scale biofloc system. Two stocking densities of tilapia were tested, 35 and 65 fish m-3 in a recirculating system with 10 m3 tanks for shrimp culture and 4 m3 for tilapia culture with water recirculation of 965.66 ± 92.83 L h-1 during 78 days. The initial weight of shrimp was 0.9±0.1 g and of tilapia was 7.1±3.2 g. Shrimps were fed according to the feeding table and fish were underfed to stimulate bioflocs consumption. Selected water quality parameters were monitored during the trial. Tilapia densities did not affect shrimp growth (11.5±1.9 g and 10.1±0.7 g for 35 and 65 fish m-3 treatments, respectively). The tilapia presented a FCR lower than 1, proving that bioflocs were consumed by fish. The clarification time was shorter when compared to other studies with shrimp monoculture. Between the treatments, a reduction of 10 hours in the system clarification occurred when lower fish stocking density was used. The results demonstrate the feasibility of integrated shrimp and tilapia culture on a pilot scale, without compromising shrimp productivity.